EXPLORING THE EFFECTIVENESS AND STUDENTS’ PERCEPTIONS OF E-LEARNING IN ENGLISH AS SECOND LANGUAGE (ESL) SPEAKING CLASSES AMIDST COVID-19 - Iziana Hani Ismail; Nur Anneliza Abd Latip; Wardatul Akmam Din; Suyansah Swanto, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The COVID-19 outbreak quickly demonstrates the importance of adopting online education in teaching and learning. It has forced education systems worldwide to find alternatives to face-to-face interactions. Language instructors have made attempts to explore and utilise e-learning tools to enrich their teaching and assist learners in improving their language learning. This paper, therefore, attempts to shed light on the effectiveness of adopting e-learning tools in ESL speaking class and their perception of it. Fifty-three pre-university students from the Foundation Programme of the Preparatory Centre for Science and Technology were involved in this study. Data analysed in this paper were derived from a threaded online discussion via Dotstorming. The structured interview questions were carefully designed based on the objectives to elicit the students’ opinions on the topic of interest. To explore the effectiveness of e-learning in developing the students’ speaking skills, scores of Individual Speaking Assessment and Group Speaking Assessment of each student were collected. These assessments were marked based on the Malaysian University English Test (MUET) Speaking Rubric – Task Fulfilment, Language, and Communicative Ability. The findings show that the adoption of technology in ESL speaking classes improves the students’ speaking abilities. The thematic analysis also shows that the use of e-learning tools in language learning received positive feedbacks from the students, suggesting it would be a promising virtual platform to improve the student's confidence, knowledge, and language.